PHOSPHORUS SORPTION KINETIC ON ACID UPLAND SMECTITIC SOIL AMENDED WITH CALCIUM CARBONATE AND CALCIUM SILICATE - Arief Hartono (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Acid upland smectitic soil is identified by high amount of exchangeable Al due to the weathering of aluminum (Al) octahedral layer by H+ saturation and by very low phosphorus (P) status.  Calcium carbonate (CaCO3) and calcium silicate (CaSiO3) were commonly used to decrease exchangeable Al and increase soil pH.  Laboratory experiments were conducted with clayey smectitic Typic Paleudults from Gajrug region, West Java.  The CaCO3 and CaSiO3 were added at rates to replace 0, 1.5 or 3 times of exchangeable Al. After one month of incubation, P sorption kinetic experiments were conducted.   The changes in some chemical properties after one month incubation showed that both CaCO3 and CaSiO3 increased the soil pH, exchangeable Ca, and base saturation  but did not increase the cation exchange capacity.  The results of the experiment showed that both CaCO3 and CaSiO3 decreased the rate constant value of first order kinetic equation (k) and the P sorbed maximum (a) at given amount of added P compared to Control.The CaCO3 was better than CaSiO3 in decreasing k values and on the contrary for a values. The decrease in P maximum sorption and the rate constant of the soil amended with CaSiO3 and CaCO3 due to occupation of P sorption sites by silicates and hydroxyl ions. The CaCO3with the rate to replace 1.5 x exchangeable Al was recommended to decrease the rate constant of P sorption. However, the CaSiO3 at the rate to replace 3 x exchangeable Al was recommended to decrease the maximum P sorption.